An unusual [4 + 2] fusion strategy to forge meso-N/O-heteroarene-fused (quinoidal) porphyrins with intense near-infrared Q-bands. Issue 30 (25th June 2019) - Li, Chengming; Zhu, Lei; Liang, Wenbo; Su, Rongchuan; Yin, Jiangliang; Hu, Yanmei; Lan, Yu; Wu, Di; You, Jingsong
Abstract : Divergent synthesis of meso-N / O -heteroarene-fused (quinoidal) porphyrins was established via rhodium-catalyzed β-C–H activation/annulation of quinoidal porphyrins with alkynes. Abstract : Here we present a divergent synthesis of brand-new types of meso-N / O -heteroarene-fused (quinoidal) porphyrins through Rh-catalyzed β-C–H activation/annulation of 5, 15-dioxoporphyrins and dioxime derivatives with alkynes, in which the synthetic disconnections are difficult to access through the commonly used intramolecular cyclization strategy. Using the O -methyl oxime as a traceless oxidizing directing group, the meso-N -embedded pyridine-fused anti -quinoidal porphyrin3 and pyridinium-fused cation4 are formed with controllable chemoselectivity and complete anti -selectivity. Replacing the exocyclic oxime with a carbonyl group delivers the pyran-fused porphyrin5, achieving structural conversion from a quinoidal conformation to a stable porphyrin macrocycle. Further oxidation of the expanded dimer5ea gives the oxonium6, which exhibits intense near-infrared (NIR) Q-bands up to 1300 nm. Theoretical studies demonstrate that the incorporation of a heteroatom at the meso -position enables more effective π-extension, resulting in a 22π aromatic ( vs. 18π aromatic) character of pyran-fused porphyrins ( syn / anti -5aa ). Compared with the commercially available methylene blue (MB ), syn -5al exhibits a better ability ( Φ Δ = 0.61) to sensitize singlet oxygen ( 1 O2 ) when irradiated with a 680 nm laser beam, and has potential as a photodynamic therapy (PDT) photosensitizer in the body's therapeutic window (650–900 nm).